THE IMPACT OF AUDITOR CHARACTERISTICS ON THE QUALITY OF FINANCIAL REPORTS, TAKING INTO ACCOUNT THE ROLE OF THE COMPANY'S STRATEGY-CASE STUDY OF COMPANIES LISTED ON THE IRAQI STOCK EXCHANGE - Dr.Siraj Razrazooqi abbas (Scholar Express Journals, 2025)
This study examines the relationship between auditor characteristics and financial reporting quality, considering the role of company strategy. The statistical population of this research includes all companies listed on the Iraq Stock Exchange. Using systematic elimination, 35 companies were selected for the period from 2009 to 2021. The research hypotheses were tested using a multivariate regression model based on combined data. The results indicate that auditor rotation has a positive effect on financial reporting quality. Additionally, the results show that business strategy positively influences the relationship between auditor rotation and financial reporting quality.
Keywords: hypotheses; relationship; financial reporting